Russian visitors to South Africa one hundred and ten years ago (Historia, 2021)
One  wonders   how   many   South  Mricans    are  aware   of  the   fact   thatRussian  blood  has  flowed   in  the  veins  of  some  of  their  Cape  Coloureds  fornearly   one  hundred   and   fifty    years.    "A   few   Russian  names  persist   inSimonstown   to   this   day",   says  Mr.   D.   H.   Varley   who   has  done  someresearch  on  this   matter. That   is   not  surprising    for   a   Russian   soldier,captured by  the  French in  1814 and  again captured by  the  English at theBattle   of   Waterloo,   was  later  brought   by   them  to  the  Cape.    He  settledthere,  married   a  "black   woman"  and  had  six  children  by  her.    The  meetingwith  this  man,  grown  old  by  1853,  is  one  of  the  minor   incidents  describedby  the  Russian  writer   Ivan   Alexandrevich    Goncharov   (1812-1891)   in  thechapter  At  the  Cape  of   Good  Hope   of  his  book  Fregat   Pallada   (FrigatePallas)    which  was  published   in  Russia  in  1856.= A   good,  and  evidently   the  only   existing   tra
Keywords: South Africa; Ivan Alexandrevich Goncharov; Fregat Pallada; Russians; Cape of Good Hope